"A Moment of Protest Becomes a Curricular Object". Issue 1 (2nd January 2020) - Spillers, Hortense J.
Abstract : A speech delivered as the keynote address at Brandeis University's AAAS 50th Anniversary, where Hortense Spillers received Brandeis University's Alumni Achievement Award on February 11, 2019. 1